African Canadian leadership continuity, transition, and transformation - Kitossa, Tamari; Lawson, Erica S. 1967-; Howard, Philip S. S. 1964- (University of Toronto Press, 2019)
"Drawing on original work from leading African-Canadian academics across Canada and internationally, this book critically explores the challenges, prospects, and ongoing achievements of Black leadership in Canadian as it responds to the needs of African Canadians. Despite diversity in nationality and patterns of immigration and settlement and other factors that differentiate African Canadians from each other, leadership has long been an important issue as African Canadians confront the uniform problem of anti-blackness in Canada. The turn of the 21 Century has brought about a"changing of the guard" in Black leadership in this country. Confronted by the passing of eminent leaders such as Rose-Marie Brown, Charles Roach, Dudley Laws, Rocky Jones, and by the current virtual absence of Black electoral representations, there is a growing sense that Black leadership in Canada is in crisis or facing a serious deficit. This collection aims to counter the "crisis" and "deficit" narratives by positioning African-Canadian leadership as a vital but rarely appreciated element of Canada's civic culture. Overall, this book critically engages the foregoing issues and questions through a multidisciplinary exploration the challenges, prospects, and ongoing achievements of Black leadership in Canada as it responds to the shifting needs of African Canadians and other Canadians."--